THE IDEAL PROFILE (INCREASE IN B-LINES/DELTA B-LINES) ON LUNG ULTRASOUND FOR DIAGNOSING WEANING INDUCED PULMONARY EDEMA IN VENTILATED PATIENTS - Rasheed, Ghulam; Shad, Zahid Siddique; Mehreen, Tooba; Kharadi, Nusrat; Ramzan, Moazma; Abdullah, Azmat; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To ascertain the ideal number of B-lines on lung ultrasound for the diagnosis of weaning induced pulmonary edema in ventilated patients.Study Design: Prospective observational study.Place and Duration of Study: Department of Medicine, Shifa International Hospital, Islamabad, from Jan to Aug 2020.Methodology: All the patients over the age of 18 years who were on mechanical ventilation in a medical intensive care unit were included in the study. The patients were given spontaneous breathing trials as a protocol for weaning from mechanical ventilation. Lung ultrasound was performed on 4 points of anterior chest wall before and after spontaneous breathing trials. Before and after spontaneous breathing trials counting of B lines was done on ultrasound of lung and comparison of increase in B lines (Delta-B-lines) was done with reference diagnosis of weaning induced pulmonary edema diagnosed by intensivist who was blinded to the results of lung ultrasound.Results: The study included 42 patients including 23 (54.8%) men and 19 (45.2%) women. 14 cases failed spontaneous breathing trials. Seven cases (16.7%) had weaning induced pulmonary edema. Delta-B-lines ≥6 diagnosed weaning induced pulmonary edema with 100% accuracy. Out of the remaining seven patients with weaning failure but without weaning induced pulmonary edema, 6 (28.6%) had Delta-B-lines ≥6. The ultrasound lung technique had a 100% sensitivity profile to detect weaning induced pulmonary edema and a specificity of 77.78%.Conclusion: The study indicates that Delta-B-lines ≥6 diagnosed the weaning induced pulmonary edema with the best accuracy.